1992
DOI: 10.1002/cne.903220405
|View full text |Cite
|
Sign up to set email alerts
|

Selective vulnerability of the hippocampal pyramidal neurons to hypothyroidism in male and female rats

Abstract: Thyroid hormone deficiency has long been considered to affect profoundly such cognitive functions as learning and memory, which are known to depend on the structural integrity of the hippocampal formation. Since we previously found that the number of granule cells of the dentate gyrus is reduced in hypothyroid animals, we decided to extend our observations to the pyramidal cells of the hippocampus in order to gain further insight into the effects of hypothyroidism upon the other neuronal links of the hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 88 publications
8
57
1
Order By: Relevance
“…Maturation and synaptic development of the pyramidal cells of the hippocampus are particularly sensitive to thyroid hormone deficiency during fetal/perinatal development (18). Early in fetal development (rats), thyroid hormone deficiency decreases radial glial cell maturation and therefore impairs cellular migration (19) …”
Section: Congenital Hypothyroidismmentioning
confidence: 99%
“…Maturation and synaptic development of the pyramidal cells of the hippocampus are particularly sensitive to thyroid hormone deficiency during fetal/perinatal development (18). Early in fetal development (rats), thyroid hormone deficiency decreases radial glial cell maturation and therefore impairs cellular migration (19) …”
Section: Congenital Hypothyroidismmentioning
confidence: 99%
“…However, only in CA1 the total 50 number of pyramidal neurons was reduced by adult hypothy-51 roidism [26]. Nevertheless, Alva-Sánchez et al [27] found that short-term adult-onset hypothyroidism impairs 56 dendritic arborization of immature neurons.…”
mentioning
confidence: 99%
“…In adulthood, hypothyroidism also decreases the weight of 48 the hippocampus [25,26] and the volume of the pyramidal neurons in CA3 and CA1 [26]. However, only in CA1 the total 50 number of pyramidal neurons was reduced by adult hypothy-51 roidism [26].…”
mentioning
confidence: 99%
“…At the morphological level, in the mature brain thyroid hormone excess (149) as well as deficiency (150) have been reported to decrease the number of dendritic spines, assumed to represent postsynaptic endings, already after 5 days in adult rats. Even more dramatically, hypothyroidism leads to a reduction of the neuropile in CA1 and CA3 hippocampal areas and in addition to a loss of pyramidal cells in the CA1 area (151). Thus it seems possible that adult-onset hypothyroidism may actually cause neuronal degeneration, as already occasionally observed in autopsies of early cases of patients who had died with myxedema (152,153).…”
Section: Explanations Of Thyroid Hormone Effects On the Brain At The mentioning
confidence: 90%